Cost Estimates for Human Immunodeficiency Virus (HIV) Care and Patient Characteristics for Health Resource Use From Linkage of Claims Data With the Swiss HIV Cohort Study. (18th July 2018) - Leon-Reyes, Selene; Schäfer, Juliane; Früh, Mathias; Schwenkglenks, Matthias; Reich, Oliver; Schmidlin, Kurt; Staehelin, Cornelia; Battegay, Manuel; Cavassini, Matthias; Hasse, Barbara; Bernasconi, Enos; Calmy, Alexandra; et al.
Abstract: Background: Comprehensive and representative data on resource use are critical for health policy decision making but often lacking for human immunodeficiency virus (HIV) infection. Privacy-preserving probabilistic record linkage of claim and cohort study data may overcome these limitations. Methods: Encrypted dates of birth, sex, study center, and antiretroviral therapy (ART) from the Swiss HIV Cohort Study (SHCS) records for 2012 and 2013 were linked by privacy-preserving probabilistic record linkage with claim data from the largest health insurer covering 15% of the Swiss residential population. We modeled predictors for mean annual costs adjusting for censoring and grouped patients by cluster analysis into 3 risk groups for resource use. Results: The matched subsample of 1196 patients from 9326 SHCS and 2355 claim records was representative for all SHCS patients receiving ART. The corrected mean (standard error) total costs in 2012 and 2013 were $30462 ($582) and $30965 ($629) and mainly accrued in ambulatory care for ART (70% of mean costs). The low-risk group for resource use had mean (standard error) annual costs of $26772 ($536) and $26132 ($589) in 2012 and 2013. In the moderate- and high-risk groups, annual costs for 2012 and 2013 were higher by $3526 (95% confidence interval, $1907–$5144) (13%) and $4327 ($2662–$5992) (17%) and $14026 ($8763–$19289) (52%) and $13567 ($8844–$18288) (52%), respectively. Conclusions: In a representative subsample of patients from linkage of SHCS and claim data, ART was the major cost factor, but patient profiling enabled identification of factors related to higher resource use. Abstract : Probabilistic record linkage of Swiss HIV Cohort Study data and claim data from the largest health insurer in Switzerland resulted in a representative subsample that allowed for patient profiling for high resource use. Antiretroviral therapy was the highest cost factor.